Field Performance of Two Orange-fleshed Sweet Potato Clones (CIP-440001 and CIP-440014) in Bangladesh - Mohanta, Haridas Chandra; Hossain, Mohammad -; Bhuiyan, Md Khalilur Rahman; Alam, Md Shamsul -; Noor, Shamsun -; Rahaman, Ebna Habib Md Shofiur; Attaluri, Sreekanth - (JOURNAL OF ROOT CROPS, 2016)
Abstract This article reports the yield performance in the regional and farmer’s field trials of two orange fleshed sweet potato (OFSP) genotypes viz., ‘CIP-440001’ and ‘CIP-440014’ introduced from the International Potato Centre (CIP) which were released as ‘BARI SP-12’ and ‘BARI SP-13’ respectively by the National Seed Board (NSB), Ministry of Agriculture, Bangladesh in 2013. The leaf colour of BARI SP-12 is green when mature, with slightly purple young leaves, triangular and 3-5 very slight leaf lobes, edge of leaf, leaf petiole and stem is slightly purple. Tuber is medium sized with Purple-brown skin and deep orange flesh. The clone CIP 440001 (BARI SP-12) contains about 14,700 IU of Beta carotene per 100g edible portion of tuber. The leaf of BARI SP-13 is green when mature, slightly purple young leaves, 5-7 deep lobes light green, leaf vine and petiole and stem light green. Tuber is medium sized with yellow brown skin and flesh Intermediate orange. The clone CIP 440014 (BARI SP-13) contains about 4,400 IU of Beta carotene per 100g edible portion of tuber. The tuber yield potential of two varieties varied between 35 and 40 t ha-1 and was superior to previously released sweet potato varieties in Bangladesh.